PERHITUNGAN HARGA POKOK PENJUALAN DAN PENENTUAN HARGA JUAL PRODUK LEMON SEREH PADA UMKM AJR - Imelda, Elsa (Jurnal Bakti Masyarakat Indonesia, 2022)
During the Covid-19 pandemic, many SMEs were af ected. The impact is generally in the form of a decrease in sales, causing MSMEs to be unable to survive. AJR is one of the MSMEs that has also been af ected by Covid-19. Usually AJR sells fried chicken and other food for lunch for the employees who work in of ice buildings at AJR's front of ice. However, since WFH (Work From Home), almost no sales per day except from online orders. The owner of AJR then tried to make other products that could be sold during the pandemic. Currently, frozen pop chicken products, chili sauce and beverage products have been developed. One of the beverage products developed is Lemonade and Lemongrass drink. The Lemonade and Lemongrass drink product from AJR is one of the packaging product developments during the Covid-19 pandemic. The benefits of Lemonade and Lemongrass can increase endurance and many other benefits so that it is one of the mainstay products to be promoted which is very useful for preventing Covid-19. However, there is a problem with this MSME owner, namely determining the selling price in order to compete with other competitors. The determination of the selling price cannot be separated from how much the cost of goods sold is issued. The PKM Untar team helped find the best alternative among various alternative production cost calculations to calculate the cost of goods sold. In addition, the PKM Untar team also helps choose the right markup price method to determine the selling price so that it can still compete with similar products. The PKM team also provided a template in the form of Microsoft Excel to enter costs so as to facilitate the calculation of production costs. Finally, the PKM team also provides knowledge about the types of non-production costs if in the future there are more and more products produced by AJR so it is necessary to divide the non-production costs. ABSTRAK: Saat pandemi Covid-19, banyak UMKM yang terkena dampak. Dampak umumnya berupa penurunan penjualan sehingga menyebabkan UMKM tidak mampu bertahan. AJR merupakan salah satu UMKM yang juga terkena dampak Covid-19. Biasanya AJR menjual ayam goreng dan makanan lainnya untuk makan siang para karyawan yang bekerja di gedung perkantoran di dpn AJR. Namun sejak WFH (Work From Home), nyaris penjualan per harinya hampir tidak ada kecuali dari pesanan online. Pemilik AJR kemudian berusaha membuat produk lainnya yang dapat dijual saat pandemi. Saat ini telah dikembangkan produk ayam pop frozen, sambal dan produk minuman. Salah satu produk minuman yang dikembangkan adalah minuman Lemon Sereh. Produk minuman Lemon Sereh dari AJR merupakan salah satu pengembangan produk kemasan di kala pandemi Covid-19 merebak. Manfaat Lemon Sereh dapat meningkatkan daya tahan tubuh dan banyak manfaat lainnya sehingga merupakan salah satu produk andalan untuk dipromosikan sangat bermanfaat untuk mencegah Covid-19. Namun terdapat permasalahan pemilik UMKM ini, yaitu penentuan harga jual agar dapat bersaing dengan pesaing lainnya. Penentuan harga jual tidak terlepas dari berapa harga pokok penjualan yang dikeluarkan. Tim PKM Untar membantu mencarikan alternatif terbaik di antara berbagai alternatif perhitungan biaya produksi untuk menghitung harga pokok penjualan. Selain itu tim PKM Untar juga membantu memilihkan metode harga markup yang tepat untuk menentukan harga jual sehingga masih dapat bersaing dengan produk sejenis. Tim PKM juga memberikan template dalam bentuk Microsoft Excel untuk memasukkan biaya sehingga memudahkan perhitungan biaya produksi. Terakhir tim PKM juga memberikan pengetahuan mengenai jenis biaya non produksi jika kelak sudah makin banyak produk yang dihasilkan oleh AJR sehingga perlu membagi biaya non produksi tersebut.